Metodologias para o Ensino de Funções Polinomiais do 1º e 2º grau no Novo Ensino Médio - Caripuna, Carlene Barroso (Brasil, 2023)
This work emerged from observations obtained at classroom, in Deputed State School João Valério of Oliveira, in the district of Itacoatiara-AM. The students, not just from 1st grade of high school, but also students of the 2nd grade of high school were afraid of subjects to containing graphs, because they didn't know how to interpret the information contained therein. Such problem left them at a disadvantage in an evaluation, because even those students that had a mathematical domain, in the subjects with graphs or even tables, if they felt lost and frustrated for they dominate not that competence important in the resolution of exercises. Soon this work was developed seeking in a short period of time to solve that deficiency or at least to minimize. With that, it was thought about working the basic, in other words, that is, to return to the concepts of polynomial of 1st and 2nd degree, working the necessary elements for the sketch of their graphs, and the disposition of the orderly pairs obtained in tables. Similar to reaching the objectives of the work she opted to work, with some methodologies, some considered traditional and another activate, idealizing that all the participants could understand the approached theme. Then it was worked an expository class and dialogued on the concepts of functions polynomials, in the sequence it was worked, rotation for stations, that it is a methodology activates, that he/she seeks to leave the students in the center of his/her learning and the teacher being just the mediator. And to contain it was worked with the educational software GeoGebra, for that, the laboratory of computer science of the school was used, something that by itself is already interesting, due to the little use of the laboratory in pedagogic activities. As a result, it was found that students assimilated the contents more and thus gained more confidence when dealing with exercises containing graphs or tables.